The combination of cyclosporine and mycophenolate mofetil is less effective than cyclosporine and methotrexate in the prevention of acute graft‐versus host disease after stem‐cell transplantation from unrelated donors. Issue 3 (1st February 2017) - Yerushalmi, Ronit; Shem‐Tov, Noga; Danylesko, Ivetta; Shouval, Roni; Nagler, Arnon; Shimoni, Avichai
Abstract: Acute graft‐versus‐host disease (GVHD) is the major treatment‐related complication after stem‐cell transplantation (SCT) from unrelated‐donors. Several GVHD prophylaxis regimens have been explored, but no regimen has shown superiority. We analyzed transplantation outcomes in 472 consecutive unrelated‐donor SCT recipients, using cyclosporine/methotrexate (MTX, n = 314) or cyclosporine/mycophenolate‐mofetil (MMF, n = 158) for GVHD prophylaxis. Neutrophil engraftment was faster after MMF, days 11 and 14, respectively ( P = .001). Acute GVHD grade II‐IV and III‐IV occurred in 47% and 28% after MMF compared to 27% and 12% after MTX, respectively ( P < .001). Nonrelapse mortality (NRM) was 44% and 24%, respectively ( P < .001). Death associated with GVHD occurred in 25% and 8% ( P < .0001), while other NRM causes occurred in 19% and 16%, respectively ( P = .39). Relapse mortality was similar. Overall survival was better after MTX, 40% and 29%, respectively ( P = .006). However, this difference had only borderline significance when adjusting for differences in patient characteristics (HR, 1.3, P = .08). To minimize potential selection bias we analyzed outcomes on the basis of an intention‐to‐treat like analysis. During the years 2008‐2009, the leading GVHD prophylaxis regimen for unrelated‐donor SCT included MMF (89% of transplants). During the other periods, MTX was used predominantly (82% of transplants). The two periods were otherwise well‐matched. Acute GVHD occurred more often in 2008‐2009. Death associated with GVHD occurred more often, while other NRM causes occurred less often resulting in similar NRM and overall survival. In conclusion, cyclosporine/MMF is associated with faster engraftment and possibly with less organ toxicity than cyclosporine/MTX. However, it is associated with increased rates of acute GVHD and GVHD‐associated deaths.